Pengembangan Bahan Ajar Berbasis Kearifan Lokal Bagi Guru MI di Kota Semarang - Ali Imron; Ma'as Shobirin (LP2M of Institute for Research and Community Services - UIN Walisongo, 2021)
The teacher in learning has a dual role as a guide, director, motivator, supervisor and designer as well as executor. Increasing the ability to develop teaching materials as an illustration of the changes that occur in students based on the local wisdom of a community also needs to be done. The purpose of writing articles from this mentoring activity is to: 1) find out how the development of teaching materials based on local wisdom for MI teachers in Semarang City, 2) find out the various potentials of local wisdom that have educational value in Semarang City The results of the MI teacher mentoring activities in developing teaching materials based on local wisdom are: 1) The implementation of activities focused on mentoring teachers in developing teaching materials based on local wisdom through an asset-based approach. Activities involving MI teachers in the city of Semarang. The form of activities carried out were FGD and practical training and evaluation and monitoring, the implementation of activities at the Micro Teaching Laboratory of the Faculty of Religion, Wahid Hasyim University. 2) The material of local wisdom if grouped based on its characteristics into 3, namely: local figures (ulama) Semarang and around, Heritage (historical buildings) and culture. There are several scholars in Semarang and its surroundings who are visited by many or the community's pilgrimage destinations, including: Kiai Sholeh Darat, Mbah Mudzakkir, Mbah Shodiq Jago and Syekh Jumadil Kubro. Meanwhile, several historical buildings as relics and become tourist destinations include: Lawang Sewu, Ronggowarsito Museum, Sampo Kong, belenduk church, and old buildings around the old city of Semarang. The culture that is maintained and carried out regularly and properly includes: Nyadran, Ritual Offerings Rewandha Goa Kreo, Dugderan. Guru dalam pembelajaran memiliki peran ganda sebagai pembimbing, pengarah, pemotivasi, pengawas dan perancang sekaligus pelaksana. Meningkatkan kemampuan dalam mengembangkan bahan ajar sebagai gambaran perubahan yang terjadi pada peserta didik bersumber pada kearifan lokal suatu masyarakat juga perlu dilakukan. Tujuan penulisan artikel dari kegiatan pendampingan ini adalah untuk: 1) mengetahui bagaimana pelaksanaan pengembangan bahan ajar berbasis kearifan lokal bagi guru MI di Kota Semarang, 2) mengetahui berbagai potensi kearifan lokal yang memiliki nilai edukatif yang ada di Kota Semarang. Hasil dari kegiatan pendampingan guru MI dalam mengembangkan bahan ajar berbasis kearifan lokal adalah: 1) Pelaksanaan kegiatan fokus pada pendampingan guru dalam mengembangkan bahan ajar berbasi kearifan lokal melalui pendekatan berbasis aset. Kegiatan melibatkan guru MI di Kota Semarang. Bentuk Kegiatan yang dilaksanakan adalah FGD dan Pelatihan praktik dan evaluasi serta monitoring, pelaksanaan kegiatan di Laboratorium Micro Teaching Fakultas Agama Universitas Wahid Hasyim. 2) Materi kearifan lokal tersebut apabila dikelompokkan berdasarkan karakteristiknya menjadi 3, yaitu: tokoh (ulama) Lokal Semarang dan sekitar, Peninggalan (bangunan sejarah) dan Kebudayaan. Terdapat beberapa ulama di Semarang dan Sekitarnya yang banyak dikunjungi atau tujuan ziarah masyarakat antara lain: Kiai Sholeh Darat, Mbah Mudzakkir, Mbah Shodiq Jago dan Syekh Jumadil Kubro. Sedangkan beberapa bangunan bersejarah sebagai peninggalan dan menjadi tujuan wisata antara lain: Lawang Sewu, Museum Ronggowarsito, Sampo Kong, Gereja Blenduk, dan bangunan tua di sekitar kota lama Semarang. Adapun kebudayaan yang terjaga dan terlaksana secara rutin dan dengan baik diantaranya: Nyadran, Ritual Sesaji Rewandha Goa Kreo, Dugderan.